Effect of soil moisture content and the irrigation frequency on the sugarcane germination - Rodrigues Moreira, Divino; José Mendes Cardoso, Victor (Pesquisa Agropecuaria Brasileira, 1998)
The aim of this work was to observe the interaction between soil moisture and irrigation time intervals on the germination of sugarcane cv. RB785148 sets in semi-controlled conditions. One-bud sets of the variety RB785148 were germinated in ceramic pots filled with soil under a transparent PVC cover using soil humidity levels of 22, 25 and 30%, that were restored at intervals of 7, 14 and 21 days. The experiment was carried out at three different periods of the year: May-June/94; Oct.-Nov./94; and Mar.-Apr./95. The results indicate that the germination decreased mainly in function of the decrease in soil humidity, whereas irrigation interval have no statistical effect on germination. An interaction between humidity level and irrigation interval was observed. A variation of the timecourse of the germination could be observed when the results of the experiments installed at different dates were compared.